Stanley : the impossible life of Africa's greatest explorer - Jeal, Tim. (New Haven [Conn.] : Yale University Press, 2007)
We think of Stanley as a cruel imperialist who connived with King Leopold II of Belgium in horrific crimes against the people of the Congo--and the journalist who conducted the most legendary celebrity interview in history, opening with, "Dr. Livingstone, I presume?" But these perceptions are not quite true, as biographer Jeal shows. With access to previously closed Stanley family archives, Jeal reveals the extent to which Stanley's career and life have been misunderstood and undervalued. Few have started life as disadvantaged as Stanley. Rejected by both parents and consigned to a Welsh workhouse, he emigrated to America as a penniless eighteen-year-old. Jeal re-creates Stanley's rise to success, his friendships and romantic relationships, and his life-changing decision to assume an American identity. Stanley's epic but unfairly forgotten African journeys are described, establishing the explorer as the greatest to set foot on the continent.--From publisher description.
Dreams of love and freedom -- In the name of the father -- A terrible freedom -- An accident-prone apprenticeship -- War correspondent -- How are we to be married? -- The long-imagined quest -- 'I cannot die!' -- Canonizing Dr Livingstone -- 'Fame is useless to me' -- A destiny resumed -- Love and the longest journey -- The island of death -- 'The great struggle with this mystery' -- 'I hate evil and love good' -- A colony for a king -- A banquet in Paris -- After the slave raids -- Who stole the Congo? -- A pawn in great power politics -- 'A king of innocence' -- Why rescue Emin Pasha? -- A fateful decision -- The enigma of Emin Pasha -- 'Evil hangs over this forest...' -- Keeping Emin Pasha's secret -- The shape of things to come... -- Dorothy's other love -- Was the Emin Pasha expedition piratical? -- Africa or a child -- An end to 'noble objects' -- Stanley, Leopold and the atrocities -- 'Before it is too late.'
"Published in 2007 in the United Kingdom by Faber and Faber" -- T.p. verso.
Maps: The search for Livingstone, 1871-1872 ; The great Trans-Africa journey, 1874-1877; Emin Pasha relief expedition, 1887-1889.
Includes bibliographical references (p. 478-487) and index.
Keywords: Stanley, Henry M. -- 1841-1904.; Livingstone, David, -- 1813-1873.; Léopold -- II, -- King of the Belgians, -- 1835-1909.; Stanley, Dorothy, -- Lady, -- -1926.; Emin Pasha, -- 1840-1892.; Explorers -- Great Britain -- Biography; Africa, Sub-Saharan -- Discovery and exploration; Africa, Central -- History -- 1884-1960.